Pengenalan Tanaman Berdampak Positif Terhadap Kesehatan Kepada Masyarakat Desa Mancilan Kecamatan Mojoagung - Airlangga, Primaadi; Susanti, Ambar; Nur Hidayat , Ardin; Masdur Rochim, Moch; Miskiyah, Zakiyatul; Triani (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Plants are grown as a beneficial organism which can be used for food, medicine, and aesthetically beautify environment around houses and big open areas. Benefits from growing plants, especially those that has positive impact on health such as medicinal herbs grown by a family and for that family, or here in Indonesia we gave them TOGA as acronym, is still not well known. Currently where the pollution is plenty; the earth climate temperature is high; and low-cost high efficiency traditional medicine is rare; the home-grown medicinal herbs or plants are greatly needed. Based on the reasoning above, we did an act to help people where we re-introduce plants that have health benefits on Mancilan village. The result of this program can be seen from the enthusiasm and spirit of innovation of PKK's members in optimizing the land around their house and making products from the results of their plant cultivation